Analysis of T5 Heat Treatment Parameters on the Hardness and Microstructure of Aluminum-Silicon Alloy - Nafi, Maula; Hartanti, Lusia Permata Sari; Aziz, Moh. Nor Ali; Wahid, Ichlas; Setiawan, Agung (Widya Teknik, 2025)
In alignment with the United Nations Sustainable Development Goal (SDG) 9 on Industry, Innovation, and Infrastructure, this study investigates methods to enhance the durability and sustainability of aluminum alloys in automotive applications, thereby reducing material waste and extending component life. Aluminum is widely used in automotive parts like engine pistons due to its beneficial properties, including lightweight, high formability, and excellent corrosion resistance. A key material in these applications is the Aluminum-Silicon (AlSi) alloy, which is known for its mechanical strength but also prone to gradual performance degradation under operational stress. Addressing this challenge, T5 heat treatment is applied to explore its impact on the alloy's microstructure and hardness, with the aim of enhancing resilience and extending the functional lifespan of automotive parts. The T5 heat treatment process involves three main stages: initial heating, sustained heating, and cooling. By exposing the AlSi alloy to varied temperatures of 240°C, 260°C, and 280°C, with a holding time of 30 minutes, this study evaluates how these temperature conditions influence the alloy's mechanical properties. The findings from Rockwell hardness testing reveal that at 240°C in SAE 40 oil at 750°C, the alloy reaches a hardness of 64.6 HRB. Similarly, at 260°C in air at room temperature, the hardness remains at 64.6 HRB, while at 280°C in water with a pH of 8 at 750°C, the hardness slightly decreases to 62.1 HRB. These results suggest that higher heating temperatures improve mechanical strength and significantly alter the microstructure of the AlSi alloy, with minor variations in hardness observed depending on cooling mediums. This study demonstrates that optimizing heat treatment can enhance both the mechanical properties and durability of AlSi alloys, contributing to the production of more resilient and sustainable automotive components in line with SDG 9 objectives.